UX-Tracking: Web and Multimodal Tool for User Experience Evaluation - Lima, Danilo Teixeira; Moura, Flavio Rafael Trindade; Alves, André Vinicius Neve; Parracho, Thiago de Moura; Zacarias, Rodrigo Oliveira; Santos, Rodrigo Pereira dos; Seruffo, Marcos César da Rocha (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2022: Anais Estendidos do XXVIII Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2022.226527, 2022)
Different markets have increasingly sought to offer personalized experiences in the use of their products and/or services. From that, this work presents UX-Tracking, a web tool for multimodal capture that adds a set of tracking techniques to allow User Experience (UX) evaluation. UX-Tracking allows you to simultaneously track mouse, eye, keyboard, history and, in the future, voice data in a single session with the user. This factor contributes to greater accuracy in UX assessments, since the interaction can be analyzed from different perspectives. As such, UX-Tranking is expected to be an alternative for researchers and professionals from academia and industry to improve quality of interaction with products and services in digital interfaces accessed via a web browser.